2020
DOI: 10.3758/s13423-020-01749-0
|View full text |Cite
|
Sign up to set email alerts
|

A-learning: A new formulation of associative learning theory

Abstract: We present a new mathematical formulation of associative learning focused on non-human animals, which we call Alearning. Building on current animal learning theory and machine learning, A-learning is composed of two learning equations, one for stimulus-response values and one for stimulus values (conditioned reinforcement). A third equation implements decision-making by mapping stimulus-response values to response probabilities. We show that A-learning can reproduce the main features of: instrumental acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 123 publications
1
21
0
Order By: Relevance
“…Second, there are trial-based models (e.g., Rescorla & Wagner, 1972) which do not explicitly code the duration of events; this appears problematic given the often reported relevance of temporal information as a learning factor in both humans and animals (e.g., Buriticá & Alcalá, 2019;Nasser & Delamater, 2016). However, a number of attempts to integrate timing into the classic trial-based models have been suggested (e.g., Delamater, Desouza, Rivkin, & Derman, 2014;Donahoe, Burgos, & Palmer, 1993;Gershman, 2015;Ghirlanda, Lind, & Enquist, 2020;Luzardo, Alonso, & Mondragon, 2017). Third, there are behavioural timing models (e.g., Killeen & Fetterman, 1988;Machado, 1997), in which agent's internal states (behavioural states) serve as events that are associated with moments in the environment at a particular time.…”
Section: Probabilities Versus Ratesmentioning
confidence: 99%
“…Second, there are trial-based models (e.g., Rescorla & Wagner, 1972) which do not explicitly code the duration of events; this appears problematic given the often reported relevance of temporal information as a learning factor in both humans and animals (e.g., Buriticá & Alcalá, 2019;Nasser & Delamater, 2016). However, a number of attempts to integrate timing into the classic trial-based models have been suggested (e.g., Delamater, Desouza, Rivkin, & Derman, 2014;Donahoe, Burgos, & Palmer, 1993;Gershman, 2015;Ghirlanda, Lind, & Enquist, 2020;Luzardo, Alonso, & Mondragon, 2017). Third, there are behavioural timing models (e.g., Killeen & Fetterman, 1988;Machado, 1997), in which agent's internal states (behavioural states) serve as events that are associated with moments in the environment at a particular time.…”
Section: Probabilities Versus Ratesmentioning
confidence: 99%
“…Besides, it can account for general observations of social learning in animals [35] and planning behavior observed in great apes and ravens [26]. In addition, this model can reproduce core features of results from animal psychology, for example instrumental and Pavlovian acquisition, conditioned reinforcement, and different kinds of higher-order conditioning [30]. The general nature of the included benchmark tests can further our knowledge of what role associative learning can play for animal intelligence.…”
Section: Introductionmentioning
confidence: 98%
“…The winner used a common three-step approach where first training environments were made, after which an agent received training, ending with a validation step involving behavior analysis. These Reinforcement Learning algorithms and recent models in animal learning research have much in common [28][29][30], and by taking both general process and adaptive specialization into account they may provide useful tools for working towards a synthesis of animal intelligence. By bridging the gap between comparative cognition and AI, The Animal-AI Olympics provide a new benchmark selection of tests different from other AI tests investigating intelligence, such as Arcade Learning Environment (ALE) [31], OpenAI Gym [32], and General Video Game AI [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations